Polyethylene copolymers for film layers

Multimodal medium density polyethylene produced by specific metallocene catalysts and two-step polymerization processes solves the problems of insufficient mechanical properties and melt homogenization of existing multimodal PE polymers in film applications, and achieves excellent mechanical properties of the film A balance between performance and sealing performance.

CN119173546APending Publication Date: 2024-12-20北欧化工公司
View PDF 20 Cites 0 Cited by

Patent Information

Application Number
CN202380039918.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-12
Filing Date
2023-05-09
Publication Date
2024-12-20

AI Technical Summary

Technical Problem

Existing multimodal PE polymers lack excellent mechanical properties in membrane applications, especially tensile modulus and impact strength, and difficulty in melt homogenization leads to uneven final products and high gel content.

Method used

Multimodal medium density polyethylene (mMDPE) is prepared using a specific metallocene catalyst, and the polyethylene components are produced through a two-step sequential polymerization process to form a film with improved mechanical properties and sealing properties.

Benefits of technology

Achieving a reduction in production costs while maintaining or improving the performance of the final product, a film with good mechanical properties and sealing properties is provided, especially showing an attractive balance in terms of tensile modulus and dart impact strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005129634670000111
    Figure BDA0005129634670000111
  • Figure BDA0005129634670000112
    Figure BDA0005129634670000112
  • Figure BDA0005129634670000121
    Figure BDA0005129634670000121
Patent Text Reader

Abstract

Metallocene catalyzed multimodal medium density polyethylene (mMDPE), the use of multimodal medium density polyethylene (mMDPE) in film applications and films comprising the mMDPE of the invention.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to metallocene-catalyzed multimodal medium density polyethylene (mMDPE), the use of multimodal medium density polyethylene (mMDPE) in film applications and films comprising the mMDPE of the invention.

[0002] State-of-the-art mLLDPE (metallocene-catalyzed linear low-density polyethylene) is widely used in daily life, such as packaging, due to its excellent cost-performance ratio.

[0003] Unimodal mLLDPE is typically used for film applications. Unimodal LLDPE has good optical properties, such as low haze, but melt processing of such polymers is not satisfactory, for example, from a production point of view and may also lead to quality problems in the final product. Multimodal mLLDPE with two or more different polymer components is easier to process, but melt homogenization of multimodal PE may be problematic, leading to inhomogeneous final products, such as high gel content in the final product.

[0004] Multimodal mLLDPE are known in the art.

[0005] WO 202100918, WO 2021009190 and WO 2021009191 of Borealis disclose a process for preparing a multimodal PE polymer in two loop reactors and a gas phase reactor in the presence of a silica-supported metallocene catalyst based on the metallocene complex bis(1-methyl-3-n-butylcyclopentadienyl)zirconium(IV) dichloride.

[0006] Film properties such as tensile modulus (TM) and impact strength (Dart Drop Impact, DDI) are not mentioned at all.

[0007] WO 2021009192 also discloses this method.

[0008] Again, there is no mention at all of the film properties such as tensile modulus (TM) and impact strength (Dart Drop Impact, DDI).

[0009] There is a growing need to find multimodal PE polymers with different balances of properties to provide tailor-made solutions that meet the growing demands of end-use producers, such as reducing production costs while maintaining or even improving the properties of the final product. There is also a need for tailor-made polymer solutions to meet the requirements of evolving equipment technologies in the end-use areas.

[0010] Therefore, there is a need in the art to provide a material having good mechanical properties, especially tensile modulus and dart drop impact strength (impact strength).

[0011] Such multimodal PE polymers should also have good sealing properties.

[0012] The present inventors have now discovered that metallocene-catalyzed medium density polyethylene (mMDPE) prepared with a specific metallocene catalyst and having a specific polymer design produces films with improved mechanical properties, especially tensile modulus and dart drop impact strength (impact strength) and an attractive balance between mechanical properties and sealing properties. Summary of the invention

[0013] Therefore, the present invention relates to a metallocene-catalyzed multimodal medium density polyethylene consisting of:

[0014] (i) 40.0 to 60.0 wt% of a polyethylene component (A) based on mMDPE, and

[0015] (ii) 40.0 to 60.0 wt% of a polyethylene component (B) based on mMDPE,

[0016] wherein the polyethylene polymer component (A) has

[0017] 950 to 980 kg / m 3 Density within range (ISO 1183);

[0018] MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 2.0 to 500.0 g / 10 min;

[0019] The polyethylene component (B) has

[0020] 900 to 925 kg / m 3 Density within range (ISO 1183);

[0021] MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.0001 to 1.0 g / 10 min; wherein the metallocene-catalyzed medium density polyethylene (mMDPE) has

[0022] 932 to 955 kg / m 3 Density in the range (ISO 1183),

[0023] MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.01 to 1.0 g / 10 min, and

[0024] MFR in the range of 25 to 100 21 Ratio of MFR (190℃, 21.6kg, ISO 1133) to MFR2 (190℃, 2.16kg, ISO1133) 21 / MFR2.

[0025] Surprisingly, such mMDPE provides films with improved mechanical properties, especially tensile modulus and dart drop impact strength (impact strength), and an attractive balance between mechanical and sealing properties.

[0026] Therefore, the present invention further relates to a film comprising at least one layer comprising an mMDPE as defined above.

[0027] definition

[0028] Where the term "comprising" is used in the present description and claims, it does not exclude other, not specifically stated, elements of major or minor functional importance. For the purposes of the present invention, the term "consisting of" is considered to be a preferred embodiment of the term "comprising". If a group is defined hereinafter as comprising at least a certain number of embodiments, this is also to be understood as disclosing the group, which preferably consists only of these embodiments.

[0029] Whenever the terms "including" or "having" are used, these terms are meant to be equivalent to "comprising" as defined above.

[0030] When an indefinite or definite article is used when referring to a singular noun, for example "a", "an" or "the", this includes a plural of that noun unless otherwise stated.

[0031] Metallocene-catalyzed medium density polyethylene (mMDPE) is defined in the present invention as a medium density polyethylene produced in the presence of a metallocene catalyst.

[0032] For the purposes of the present invention, "medium density polyethylene (MDPE) comprising a polyethylene component (A) and a polyethylene component (B)" means that the MDPE is produced in at least a two-step sequential polymerization process, wherein component (A) is produced first and then, in a subsequent polymerization step, component (B) is produced in the presence of component (A) to produce the MDPE, or vice versa, i.e. component (B) is produced first and then, in a subsequent polymerization step, component (A) is produced in the presence of component (B) to produce the MDPE.

[0033] MDPE produced in a multistage process is also known as an "in-situ" blend or a "reactor" blend. The resulting final product consists of an intimate mixture of polymers from two or more reactors whose different molecular weight distribution curves together form a molecular weight distribution curve with a broad maximum or two or more maxima, i.e., the final product is a multimodal polymer mixture.

[0034] In the context of medium density polyethylene (MDPE), the term "multimodal" refers herein to the multimodality of the melt flow rate (MFR) of at least two polyethylene components, i.e. the two polyethylene components have different MFR values. The multimodal medium density polyethylene may have additional or alternative multimodality between the two polyethylene components with respect to one or more other properties (such as density, comonomer type and / or comonomer content), which will be described hereinafter. DETAILED DESCRIPTION

[0035] Metallocene-catalyzed multimodal medium density polyethylene (MDPE)

[0036] The metallocene-catalyzed multimodal mMDPE according to the present invention has a molecular weight of 932 to 955 kg / m 3 , preferably 935 to 950 kg / m 3 , more preferably 938 to 945 kg / m 3 Density within the range (ISO 1183).

[0037] The MFR2 (190°C, 2.16 kg, ISO 1133) of the metallocene-catalyzed mMDPE is in the range of 0.01 to 1.0 g / 10 min, preferably 0.05 to 0.90 g / 10 min, more preferably 0.10 to 0.80 g / 10 min, even more preferably 0.20 to 0.70 g / 10 min.

[0038] MFR of metallocene-catalyzed mMDPE 21 (190°C, 21.6 kg, ISO 1133) is in the range of 8.0 to 50.0 g / 10 min, preferably in the range of 10.0 to 45.0 g / 10 min, more preferably in the range of 12.0 to 40.0 g / 10 min, most preferably in the range of 15.0 to 35.0 g / 10 min.

[0039] The metallocene-catalyzed mMDPE according to the present invention also has an MFR in the range of 25.0 to 100.0, preferably 35.0 to 80.0, more preferably 45.0 to 70.0. 21 / MFR2 flow rate ratio (FRR).

[0040] Furthermore, the metallocene-catalyzed MDPE may have a molecular weight distribution (MWD) Mw / Mn in the range of 4.0 to 12.0, preferably 5.0 to 11.0, more preferably 6.0 to 10.0.

[0041] The FRR / MWD ratio of the metallocene-catalyzed mMDPE according to the present invention is in the range of 5.0 to 12.0, preferably 6.0 to 11.0, more preferably 7.0 to 10.0.

[0042] In addition, the metallocene-catalyzed mMDPE according to the present invention may have one or more or all of the properties described below:

[0043] Weight average molecular weight Mw

[0044] The weight average molecular weight Mw of the metallocene-catalyzed MDPE may be at least 100,000 g / mol, preferably in the range of 102,000 to 170,000 g / mol, more preferably 105,000 to 150,000 g / mol, still more preferably 1,070,000 to 135,000 g / mol.

[0045] Z-average molecular weight Mz

[0046] The z-average molecular weight Mz may be in the range of 250,000 to 500,000 g / mol, preferably 270,000 to 450,000 g / mol, more preferably 300,000 to 400,000 g / mol.

[0047] Mz / Mw ratio

[0048] The Mz / Mw ratio may be in the range of 2.0 to 4.0, preferably 2.2 to 3.5, more preferably 2.3 to 3.2.

[0049] FRR / (Mz / Mw) ratio

[0050] The FRR / (Mz / Mw) ratio may be in the range of 12.0 to 30.0, preferably 14.0 to 26.0, more preferably 15.0 to 24.0.

[0051] Metallocene-catalyzed mMDPE consists of:

[0052] (i) 40.0 to 60.0 wt% of a polyethylene component (A) relative to the total weight of mMDPE, having a molecular weight of 950 to 980 kg / m 3 A density in the range of 1000 g / cm3 and an MFR2 (190°C, 2.16 kg, ISO 1133) of 2.0 to 500 g / 10 min; and

[0053] (ii) 40.0 to 60.0 wt% of a polyethylene component (B) relative to the total weight of mMDPE, having a molecular weight of 900 to 925 kg / m 3 The invention relates to a polymer having a density in the range of 0.0001 to 1.0 g / 10 min and a MFR2 (190°C, 2.16 kg, ISO 1133) of 0.0001 to 1.0 g / 10 min.

[0054] The sum of the amounts of components (A) and (B) is 100 wt%.

[0055] Therefore, in the metallocene-catalyzed mMDPE, the weight ratio of component (A) to component (B) is in the range of 40:60 to 60:40, preferably 42:58 to 58:42, more preferably 45:55 to 55:45.

[0056] The polyethylene components (A) and / or (B) may be homopolymers or ethylene copolymers.

[0057] Preferably, the mMDPE may have two copolymer components or one copolymer component and one homopolymer component, whereby preferably both components are ethylene copolymers, or the polyethylene component (A) is a homopolymer and the polyethylene component (B) is a copolymer, or vice versa (the polyethylene component (A) is a copolymer and the polyethylene component (B) is a homopolymer). More preferably, the polyethylene component (A) is a homopolymer and the polyethylene component (B) is a copolymer.

[0058] For the purposes of the present invention, a polyethylene homopolymer is a polymer comprising at least 99.0 wt%, in particular at least 99.5 wt% of ethylene monomer units. Thus, a polyethylene homopolymer may contain up to 1.0 wt%, but preferably only up to 0.5 wt%, for example up to 0.2 wt% or even only up to 0.1 wt% of comonomer units.

[0059] In one embodiment of the present invention, the amount of comonomer in the polyethylene homopolymer component is 13 C-NMR was undetectable.

[0060] Preferably, polyethylene component (B) is composed of a single ethylene copolymer or a single ethylene homopolymer, more preferably composed of a single ethylene copolymer. Polyethylene component (A) can be composed of a single ethylene homopolymer or copolymer. Alternatively, polyethylene component (A) can be an ethylene polymer mixture comprising a first ethylene polymer portion (A-1) and a second ethylene polymer portion (A-2) (e.g., composed thereof), wherein the two portions are either homopolymers or copolymers. Polyethylene component (A) can be unimodal or multimodal. In the case where polyethylene component (A) is an ethylene copolymer mixture, the comonomers in the preferred first and second ethylene copolymer portions are identical.

[0061] Preferred ethylene copolymers use α-olefins (e.g., C3-12 α-olefins) as comonomers. Examples of suitable α-olefins include 1-butene, 1-hexene, and 1-octene. 1-Butene and 1-hexene are particularly preferred comonomers.

[0062] Most preferably, polyethylene component (A) is a polyethylene homopolymer as defined above and polyethylene component (B) is an ethylene-1-hexene copolymer.

[0063] The MFR2 of the polyethylene component (A) is preferably in the range of 10 to 400 g / 10 min, more preferably 50 to 300 g / 10 min, even more preferably 60 to 200 g / 10 min, most preferably 70 to 150 g / 10 min.

[0064] The density of the polyethylene component (A) is preferably in the range of 955 to 975 kg / m 3 , more preferably 960 to 972 kg / m 3 , even more preferably 962 to 970 kg / m 3 within the range.

[0065] It is further preferred that the polyethylene component (A) consists of two fractions, namely a first ethylene polymer fraction (A-1) and a second ethylene polymer fraction (A-2), preferably consists of a first ethylene homopolymer fraction (A-1) and a second ethylene homopolymer fraction (A-2).

[0066] It is possible to produce fraction (A-1) first and then, in a subsequent reactor, produce fraction (A-2) in the presence of fraction (A-1), or vice versa, i.e., produce fraction (A-2) first and then, in a subsequent reactor, produce fraction (A-1) in the presence of fraction (A-2). Preferably, fraction (A-1) is produced first.

[0067] The MFR2 and / or density of fractions (A-1) and (A-2) may be the same or may be different from each other.

[0068] Thus, preferably, the MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer portion (A-1) is in the range of 5.0 to 100.0 g / 10 min, preferably 10.0 to 80.0 g / 10 min, more preferably 15.0 to 70.0 g / 10 min, even more preferably 20.0 to 60.0 g / 10 min, such as 22.0 to 50.0 g / 10 min.

[0069] The MFR2 (190°C, 2.16 kg, ISO 1133) of the ethylene polymer portion (A-2) is preferably in the range of 100.0 to 1500.0 g / 10 min, preferably 200.0 to 1200.0 g / 10 min, more preferably 250.0 to 1000.0 g / 10 min, most preferably 280.0 to 800.0 g / 10 min.

[0070] Preferably, the MFR2 of fraction (A-2) is higher than the MFR2 of fraction (A-1).

[0071] The density of the ethylene polymer portion (A-1) is preferably in the range of 945 to 970 kg / m 3 , preferably 950 to 965 kg / m3 , even more preferably 952 to 962 kg / m 3 within the range.

[0072] The density of the ethylene polymer portion (A-2) is 960 to 980 kg / m 3 , more preferably 965 to 980 kg / m 3 , even more preferably 970 to 978 kg / m 3 within the range.

[0073] Preferably, the density of fraction (A-2) is higher than the density of fraction (A-1).

[0074] The MFR2 of the polyethylene component (B) is preferably in the range of 0.0003 to 0.5 g / 10 min, more preferably 0.0005 to 0.1 g / 10 min, even more preferably 0.0008 to 0.01 g / 10 min.

[0075] The density of the polyethylene component (B) is preferably in the range of 905 to 920 kg / m 3 , more preferably 908 to 918 kg / m 3 , even more preferably 910 to 916 kg / m 3 within the range.

[0076] Metallocene-catalyzed mMDPE can be produced by polymerizing with a metallocene catalyst system using conditions that produce a multimodal (eg, bimodal) polymer product.

[0077] Therefore, the metallocene-catalyzed mMDPE of embodiment (I) can be produced in a two-stage process, preferably comprising a slurry reactor (loop reactor), wherein the slurry (loop) reactor is connected in series with a gas phase reactor (GPR), thereby producing polyethylene component (A) or polyethylene component (B) in the loop reactor, and then producing the other ethylene polymer component in the GPR in the presence of the first produced ethylene polymer component to produce metallocene-catalyzed mMDPE, preferably, polyethylene component (A) is produced in the loop reactor and polyethylene component (B) is produced in the GPR in the presence of polyethylene component (A) to produce metallocene-catalyzed mMDPE.

[0078] In case the polyethylene component (A) of the metallocene-catalyzed mMDPE consists of ethylene polymer fractions (A-1) and (A-2), the metallocene-catalyzed mMDPE may be produced in a three-stage process, which preferably comprises a first slurry reactor (loop reactor 1), wherein the first slurry loop reactor is connected in series to a further slurry reactor (loop reactor 2), such that the first ethylene polymer fraction (A-1) produced in loop reactor 1 is fed to loop reactor 2, where the second ethylene polymer fraction (A-2) is produced in the presence of the first fraction (A-1). Fraction (A-1) may be produced first and then, in a subsequent reactor, fraction (A-2) is produced in the presence of fraction (A-1), or vice versa, i.e., fraction (A-2) is produced first and then, in a subsequent reactor, fraction (A-1) is produced in the presence of fraction (A-2). Preferably, fraction (A-1) is produced first.

[0079] Within the scope of the present invention, the first and second ethylene polymer parts (A-1 and A-2) of the polyethylene component (A) are present in a weight ratio of 4:1 to 1:4, for example 3:1 to 1:3, or 2:1 to 1:2, or 1:1, based on the total weight of the polyethylene component (A).

[0080] The first and second polymerisation stages are preferably slurry polymerisation steps.

[0081] Slurry polymerization is usually carried out in an inert diluent, which is usually a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of these hydrocarbons. A particularly preferred diluent is propane, which may contain small amounts of methane, ethane and / or butane.

[0082] The temperature of the first and second polymerization stages is generally 60-100° C., preferably 70-90° C. Excessively high temperatures should be avoided to prevent partial dissolution of the polymer into the diluent and contamination of the reactor. The pressure is 1-150 bar, preferably 40-80 bar.

[0083] Slurry polymerization can be carried out in any known reactor for slurry polymerization. Such reactors include continuous stirred tank reactors and loop reactors. Slurry polymerization is particularly preferably carried out in a loop reactor. In such a reactor, the slurry is circulated at high speed along a closed pipeline by using a circulating pump. Loop reactors are well known in the art, and examples are given, for example, in US-A-4582816, US-A-3405109, US-A-3324093, EP-A-479186 and US-A-5391654. Therefore, it is preferred to carry out the first and second polymerization stages in the form of slurry polymerization in two continuous loop reactors.

[0084] The slurry can be withdrawn from each reactor continuously or intermittently. A preferred mode for intermittent withdrawal is to use settling legs, wherein the slurry is concentrated and then a batch of concentrated slurry is withdrawn from the reactor. The use of settling legs is disclosed in US-A-3374211, US-A-3242150 and EP-A-1310295. Continuous withdrawal is disclosed in EP-A-891990, EP-A-1415999, EP-A-1591460 and WO-A-2007 / 025640. As disclosed in EP-A-1310295 and EP-A-1591460, continuous withdrawal is advantageously combined with a suitable concentration method. Preferably, the slurry is withdrawn continuously from each of the first and second polymerization stages.

[0085] Hydrogen is usually introduced into the first and second polymerisation stages for controlling the MFR2 of the first and second ethylene polymers. The amount of hydrogen required to achieve the desired MFR depends on the catalyst used and the polymerisation conditions.

[0086] Therefore, the loop reactor 2 is connected in series to a gas phase reactor (GPR) such that the polyethylene component (A) leaving the second slurry reactor is fed to the GPR to produce a trimodal polyethylene copolymer. In this case, the reaction conditions in the two slurry reactors are selected such that products different in MFR and / or density are produced in the two slurry reactors.

[0087] The third polymerization stage is a gas phase polymerization step, ie carried out in a gas phase reactor. Any suitable gas phase reactor known in the art may be used, such as a fluidized bed gas phase reactor.

[0088] For gas phase reactors, the reaction temperature used is usually 60-115° C. (e.g. 70-110° C.), the reactor pressure is usually in the range of 10-25 bar, and the residence time is usually 1-8 hours. The gas used is usually a non-reactive gas, such as nitrogen or a low boiling hydrocarbon, such as propane and a monomer (e.g. ethylene).

[0089] A chain transfer agent, such as hydrogen, is usually added to the third polymerization stage.

[0090] Such processes are described inter alia in WO 2016 / 198273, WO 2021009189, WO 2021009190, WO 2021009191 and WO 2021009192. Full details of how to prepare suitable multimodal polymers can be found in these references.

[0091] A suitable process is the Borstar PE process or the Borstar PE 3G process.

[0092] Therefore, the metallocene-catalyzed mMDPE according to the present invention is preferably produced in a loop-loop-gas phase cascade.Such a polymerization step may be preceded by a prepolymerization step.

[0093] The purpose of prepolymerization is to polymerize a small amount of polymer onto the catalyst at low temperature and / or low monomer concentration. By prepolymerization, the performance of the catalyst in slurry can be improved and / or the properties of the final polymer can be changed. The prepolymerization step is preferably carried out in slurry. Therefore, the prepolymerization step can be carried out in a loop reactor.

[0094] Then, the prepolymerization is preferably carried out in an inert diluent, which is generally a hydrocarbon diluent, such as methane, ethane, propane, n-butane, isobutane, pentane, hexane, heptane, octane, etc., or a mixture thereof. Preferably, the diluent is a low-boiling hydrocarbon having 1 to 4 carbon atoms or a mixture of these hydrocarbons.

[0095] The temperature in the prepolymerization step is usually from 0 to 90°C, preferably from 20 to 80°C, more preferably from 45 to 75°C.

[0096] The pressure is not critical and is generally 1 to 150 bar, preferably 40 to 80 bar.

[0097] The amount of monomer is usually such that 0.1 to 1000 grams of monomer are polymerized per gram of solid catalyst component in the prepolymerization step. As known to those skilled in the art, the catalyst particles recovered from the continuous prepolymerization reactor do not all contain the same amount of prepolymer. On the contrary, each particle has its own characteristic amount, which depends on the residence time of the particle in the prepolymerization reactor. Because some particles stay in the reactor for a relatively long time, and some stay for a relatively short time, the amount of prepolymer on different particles is also different, and some single particles may contain the amount of prepolymer beyond the above range. However, the average amount of prepolymer on the catalyst is usually within the above range.

[0098] As is known in the art, the molecular weight of the prepolymer can be controlled by hydrogen.In addition, antistatic additives can be used to prevent the particles from sticking to each other or to the reactor walls, as disclosed in WO-A-96 / 19503 and WO-A-96 / 32420.

[0099] When there is a prepolymerization step, the catalyst components are preferably all introduced into the prepolymerization step. However, when the solid catalyst component and the cocatalyst can be fed separately, it is possible that only a part of the cocatalyst is introduced into the prepolymerization stage, while the rest is introduced into the subsequent polymerization stage. Moreover, in this case, it is necessary to introduce so much cocatalyst into the prepolymerization stage in order to obtain a sufficient polymerization reaction therein.

[0100] It is to be understood that within the scope of the present invention the amount of polymer produced in the prepolymerisation is within 1.0 to 5.0 wt% relative to the final metallocene catalysed mMDPE. This can be counted as part of the first polyethylene component (A).

[0101] catalyst

[0102] The metallocene-catalyzed mMDPE of the present invention is mMDPE prepared using a metallocene catalyst. The metallocene catalyst comprises a metallocene complex and a cocatalyst. The metallocene compound or complex is also referred to herein as an organometallic compound (C).

[0103] The organometallic compound (C) comprises a transition metal (M) from Groups 3 to 10 of the Periodic Table of Elements (IUPAC 2007) or from the actinides or lanthanides.

[0104] According to the present invention, the term "organometallic compound (C)" includes any metallocene or non-metallocene compound of a transition metal, which carries at least one organic (coordinating) ligand and exhibits catalytic activity alone or together with a cocatalyst. Transition metal compounds are well known in the art, and the present invention encompasses compounds of metals from Groups 3 to 10, e.g. Groups 3 to 7, or Groups 3 to 6, e.g. Groups 4 to 6, of the Periodic Table (IUPAC 2007), as well as lanthanides or actinides.

[0105] In one embodiment, the organometallic compound (C) has the following formula (I):

[0106]

[0107] Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 - alkoxy, phenyl or benzyl;

[0108] Each Het is independently a monocyclic heteroaromatic group containing at least one heteroatom selected from O or S; L is -R'2Si-, wherein each R' is independently a C substituted by an alkoxy group having 1 to 10 carbon atoms; 1-20 -Hydrocarbon or C 1-10 -alkyl;

[0109] M is Ti, Zr or Hf;

[0110] Each R 1 Same or different, is C 1-6 -alkyl or C 1-6 - alkoxy;

[0111] Each n is 1 to 2;

[0112] Each R2 Same or different, is C 1-6 -alkyl, C 1-6 -alkoxy or -Si(R)3 group;

[0113] Each R is optionally replaced by 1 to 3 C 1-6 -alkyl substituted C 1-10 - alkyl or phenyl; and

[0114] Each p is from 0 to 1.

[0115] Preferably, the compound of formula (I) has the structure

[0116]

[0117] Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 - alkoxy, phenyl or benzyl;

[0118] L is Me2Si-;

[0119] Each R 1 Same or different and C 1-6 - alkyl, for example methyl or tert-butyl;

[0120] Each n is 1 to 2;

[0121] R 2 is -Si(R)3alkyl; each p is 1;

[0122] Each R is C 1-6 -alkyl or phenyl.

[0123] Highly preferred complexes of formula (I) are

[0124]

[0125] Most preferably, the complex dimethylsilanediylbis[2-(5-trimethylsilylfuran-2-yl)-4,5-dimethylcyclopentadien-1-yl]zirconium dichloride is used.

[0126] More preferably, the polyethylene components (A) and (B) of the metallocene-catalyzed mMDPE are prepared using the same metallocene catalyst, ie in the presence of the same metallocene catalyst.

[0127] To form the catalyst, a cocatalyst, also called an activator, well known in the art is used. Cocatalysts containing Al or B are well known and can be used here. Preferably, an aluminoxane (such as MAO) or a boron-based cocatalyst (such as a borate) is used.

[0128] In contrast to Ziegler Natta catalysis, polyethylene copolymers made using single-site catalysis have characteristics that distinguish them from Ziegler Natta materials. In particular, the comonomer distribution is more uniform. This can be shown using TREF or Crystaf techniques. Catalyst residues can also be indicative of the catalyst used. For example, Ziegler Natta catalysts do not contain Zr or Hf Group (IV) metals.

[0129] The metallocene-catalyzed mMDPE may contain additives and / or fillers.

[0130] Optional additives and fillers and the amounts used are conventional in the field of film applications. Examples of such additives are, inter alia, antioxidants, processing stabilizers, UV stabilizers, pigments, fillers, antistatic additives, antiblocking agents, nucleating agents, acid scavengers and polymer processing aids (PPAs).

[0131] As mentioned above, the metallocene-catalyzed mMDPE according to the present invention provides improved mechanical properties, especially tensile modulus and dart drop impact strength (impact strength) and additionally an attractive balance between mechanical properties and sealing properties.

[0132] Therefore, the present invention further relates to a film comprising at least one layer comprising a metallocene-catalyzed mMDPE as described above.

[0133] membrane

[0134] The film of the present invention comprises at least one metallocene-catalyzed mMDPE as defined above. The film may be a monolayer film comprising the polyethylene composition defined above or a multilayer film wherein at least one layer comprises the polyethylene composition defined above. The terms "monolayer film" and "multilayer film" have well-known meanings in the art.

[0135] The film is preferably produced by any conventional film extrusion process known in the art, including cast film and blown film extrusion. Most preferably, the film is a blown film or cast film, especially a blown film. For example, blown film is produced by extruding through an annular die and blowing into a tubular film by forming bubbles, which burst between rollers after solidification. The film can then be cut, cut or converted (e.g., folded) as required. Traditional film production techniques can be used in this regard. If preferred blown film or cast film is a multilayer film, each layer is typically coextruded. The technician will know suitable extrusion conditions.

[0136] The film according to the present invention may be subjected to post-treatment processes such as surface modification, lamination or orientation processes, etc. Such orientation processes may be uniaxial (MDO) or biaxial orientation, wherein uniaxial orientation is preferred.

[0137] In another preferred embodiment, the film is non-oriented.

[0138] Preferred films according to the invention are monolayer blown films.

[0139] The thickness of the single-layer film of the present invention may be 20 to 120 μm, preferably 30 to 100 μm, and more preferably 35 to 80 μm.

[0140] The film according to the present invention has at least one or more or all of the following properties a) to c):

[0141] a) the film of the present invention may have a dart drop impact strength (DDI) measured on a 40 μm single layer test blown film according to ISO 7765-1:1988 of at least 150 g to at most 500 g, preferably 200 g to at most 450 g, more preferably 250 g to at most 400 g, and / or

[0142] b) The films according to the invention may have good stiffness (tensile modulus measured on 40 μm monolayer test blown films according to ISO 527-3), ie > 450 MPa (in both directions).

[0143] Thus, the tensile modulus of the film comprising the polyethylene composition (measured on a 40 μm monolayer test blown film according to ISO 527-3) is in the range of >450 MPa to 1000 MPa, preferably 520 MPa to 800 MPa in the machine direction (MD) and in the range of 500 MPa to 1000 MPa, preferably 600 MPa to 800 MPa in the transverse direction (TD), and / or

[0144] c) Relative Elmendorf tear resistance of the films according to the invention measured to ISO 6383 / 2 on blown films with a film thickness of 40 μm

[0145] c1) at least 10 N / mm to 50 N / mm, preferably 12 N / mm to 40 N / mm, more preferably 15 N / mm to 30 N / mm in the machine direction (MD), and

[0146] c2) at least 120 N / mm to 400 N / mm, preferably 150 N / mm to 350 N / mm, more preferably 180 N / mm to 300 N / mm in transverse direction (TD).

[0147] d) In one embodiment of the present invention, the membrane is characterized in that according to formula (I):

[0148] The improved relationship between the mechanical properties and the sealing properties determined on a 40 μm test blown film is shown in Figure 2, wherein the tensile modulus in the longitudinal direction is measured on a 40 μm test blown film at 23°C according to ISO 527-3, DDI is the dart impact strength determined on a 40 μm test blown film according to ISO 7765-1:1988, and SIT is the seal initiation temperature measured on a 40 μm test blown film as described in the experimental part.

[0149] Preferred TM(MD) * DDI / SIT>800, more preferably>1000.

[0150] The suitable upper limit of TM(MD)*DDI / SIT is 2,500, preferably 2,000, more preferably 1,500.

[0151] Preferably, the membrane according to the invention satisfies parameter d) and additionally at least parameter a), more preferably satisfies parameter d and additionally parameters a and b), even more preferably satisfies parameter d) and additionally parameters a), b) and c2).

[0152] The films according to the invention are very suitable for use in a variety of packaging applications.

[0153] Furthermore, the film according to the invention can be used as a layer in a multilayer polyethylene-based blown film, preferably as a core layer in a multilayer polyethylene-based blown film.

[0154] The present invention will be further described with reference to the following non-limiting examples.

[0155] Determination method

[0156] Unless otherwise stated in the description or the experimental section, the following methods were used to determine the properties of the polymers (including parts and components thereof) and / or any sample preparations thereof as described in the text or in the experimental section.

[0157] Melt flow rate:

[0158] The melt flow rate (MFR) is determined according to ISO 1133 and is expressed in g / 10 min. The MFR is an indicator of the flowability of the polymer and therefore of its processability. The MFR of polyethylene is determined at 190°C. The MFR can be determined at different loads, for example 2.16 kg (MFR2), 5 kg (MFR5) or 21.6 kg (MFR 21 ).

[0159] Calculation of MFR2 of component B and part (A-2)

[0160] logA=x·logB+(1-x)·logC

[0161]

[0162] For component B:

[0163] B = MFR2 of component (A)

[0164] C = MFR2 of component (B)

[0165] A = Final MFR2 of multimodal mMDPE (blend)

[0166] X = weight fraction of component (A).

[0167] For part (A-2):

[0168] B = MFR2 of the first part (A-1)

[0169] C = MFR2 of the second part (A-2)

[0170] A = Final MFR2 of cyclic polymer (= component (A)) (mixture)

[0171] X = weight fraction of the first part (A-1).

[0172] density

[0173] The density of polymers is measured according to ISO 1183 and is expressed in kg / m 3 Given, the sample preparation was carried out according to ISO 1872-2.

[0174] GPC

[0175] The average molecular weight (M z 、M w and M n ), molecular weight distribution (MWD) and its breadth described by the polydispersity index PDI = Mw / Mn (where Mn is the number average molecular weight and Mw is the weight average molecular weight) are calculated by gel permeation chromatography (GPC) using the following formula:

[0176]

[0177] For a constant elution volume interval ΔV i , where A i and M i and the elution volume V i The associated chromatographic peak slice area and the polyolefin molecular weight (MW), where N equals the number of data points obtained from the chromatogram between the integration limits.

[0178] A high temperature GPC instrument equipped with an infrared (IR) detector (IR4 or IR5 from PolymerChar (Valencia, Spain)) and equipped with 3x Agilent-PLgel Olexis and 1x Agilent-PLgel Olexis Guard columns was used. 1,2,4-Trichlorobenzene (TCB) stabilized with 250 mg / L 2,6-di-tert-butyl-4-methylphenol was used as solvent and mobile phase. The chromatographic system was operated at a constant flow rate of 1 mL / min at 160°C. 200 μL of sample solution was injected for each analysis. Data collection was performed using Agilent Cirrus software version 3.3 or PolymerChar GPC-IR control software.

[0179] The column set was calibrated using universal calibration (according to ISO 16014-2:2003) with 19 narrow MWD polystyrene (PS) standards ranging from 0.5 kg / mol to 11500 kg / mol. The PS standards were dissolved at room temperature for several hours. The conversion of polystyrene peak molecular weight to polyolefin molecular weight was accomplished by using the Mark Houwink equation and the following Mark Houwink constants:

[0180] K PS =19x 10 -3 mL / g, α PS =0.655

[0181] K PE =39x 10 -3 mL / g, α PE =0.725

[0182] K PP =19x 10 -3 mL / g, α PP =0.725

[0183] A third-order polynomial fit was used to fit the calibration data.

[0184] All samples were prepared in the concentration range of 0.5-1 mg / ml and dissolved at 160°C for 2.5 hours for PP or 3 hours for PE with continuous gentle shaking.

[0185] To exclude the influence of additives such as irganox 1010, irgafos 168 or some other low molecular weight oligomers, the low molecular weight integration limit was set at the valley between the antioxidant peak and the polymer peak (logM of the analyzed sample was about 2.8 (PE equivalent)).

[0186] Comonomer content:

[0187] Quantification of microstructure by NMR spectroscopy

[0188] Quantitative nuclear magnetic resonance (NMR) spectroscopy was used to quantify the comonomer content of the polymers.

[0189] A Bruker Avance III 400 MHz NMR spectrometer was used to analyze the 1 H and 13 C was operated at 500.13 and 125.76 MHz and quantitative data were recorded in the molten state. 13 C{ 1 H}NMR spectra. All spectra were obtained using 13 The spectra were recorded at 150 °C using a C-optimized 7 mm magic angle spinning (MAS) probe head with nitrogen used for all pneumatics. Approximately 200 mg of material was loaded into a 7 mm outer diameter zirconium oxide MAS rotor and spun at 4 kHz. This setup was chosen primarily for the high sensitivity required for rapid identification and accurate quantification {klimke06, parkinson07, castignolles09}. Standard single pulse excitation was used, utilizing NOE {pollard04, klimke06} with a short recycle delay of 3 s and an RS-HEPT decoupling scheme {fillip05, griffin07}. A total of 1024 (1k) transients were acquired for each spectrum.

[0190] Quantitative 13 C{ 1 H} NMR spectra were processed, integrated, and the relevant quantitative properties were determined from the integration. All chemical shifts were internally referenced to the bulk methylene signal (δ+) at 30.00 ppm.

[0191] The amount of ethylene is quantified using the integration of the methylene (δ+) sites at 30.00 ppm and taking into account the number of reported sites per monomer:

[0192] E=I δ+ / 2

[0193] Correction for the presence of isolated comonomer units is based on the number of isolated comonomer units present:

[0194] E total = E + (3 * B+2 * H) / 2

[0195] where B and H are defined for their respective comonomers. Corrections are made in a similar manner when there is continuous and discontinuous comonomer incorporation.

[0196] Characteristic signals corresponding to the incorporation of 1-butene were observed and the comonomer fraction was calculated as the fraction of 1-butene in the polymer relative to all monomers in the polymer:

[0197] fB total = B total / (E total + B total + H total)

[0198] Use 39.8ppm * The amount of isolated 1-butene incorporated into the EEBEE sequence was quantified by integrating the B2 sites and taking into account the number of reporter sites per comonomer:

[0199] B=I *B2

[0200] If present, the amount of continuously incorporated 1-butene in the EEBBEE sequence was quantified using the integration of the ααB2B2 site at 39.4 ppm and taking into account the number of reported sites for each comonomer:

[0201] BB=2 * IααB2B2

[0202] If present, the amount of non-continuous incorporation of 1-butene in the EEBEBEE sequence was quantified using the integration of the ββB2B2 site at 24.6 ppm and taking into account the number of reporting sites per comonomer:

[0203] BEB=2 * IββB2B2

[0204] Due to the isolated (EEBEE) and discontinuously incorporated (EEBEBEE) 1-butene * B2 and * The βB2B2 sites were overlapped separately and the total amount of isolated 1-butene incorporation was corrected based on the amount of discontinuous 1-butene present:

[0205] B=I *B2 -2 * I ββB2B2

[0206] No BBB sequence was observed. The total 1-butene content was calculated based on the sum of isolated, continuously and discontinuously incorporated 1-butene:

[0207] Total B = B + BB + BEB

[0208] The total mole fraction of 1-butene in the polymer is then calculated as:

[0209] fB=B total / (E total+B total+H total)

[0210] A characteristic signal corresponding to the incorporation of 1-hexene was observed and the comonomer fraction was calculated as the fraction of 1-hexene in the polymer relative to all monomers in the polymer:

[0211] fH total = H total / (E total + B total + H total)

[0212] Use 38.3ppm * The amount of isolated 1-hexene incorporated into the EEHEE sequence was quantified by integrating the B4 sites and taking into account the number of reporter sites per comonomer:

[0213] H=I *B4

[0214] If present, the amount of continuously incorporated 1-hexene in the EEHHEE sequence was quantified using the integration of the ααB4B4 site at 40.5 ppm and taking into account the number of reporter sites for each comonomer:

[0215] HH=2 * IααB4B4

[0216] If present, the amount of non-continuous incorporation of 1-hexene in the EEHEHEE sequence was quantified using the integration of the ββB4B4 site at 24.7 ppm and taking into account the number of reporter sites per comonomer:

[0217] HEH=2 * IββB4B4

[0218] No HHH sequence was observed. The total 1-hexene content was calculated based on the sum of isolated, continuous and discontinuously incorporated 1-hexene:

[0219] Total H = H + HH + HEH

[0220] The total mole fraction of 1-hexene in the polymer was then calculated as:

[0221] fH=H total / (E total+B total+H total)

[0222] The mole percentage of comonomer incorporation is calculated from the mole fraction:

[0223] B [mol%] = 100 * f

[0224] H [mol%] = 100 * f

[0225] The weight percent of comonomer incorporation is calculated from the mole fraction:

[0226] B [wt%] = 100 * (fB * 56.11) / ((fB* 56.11)+(fH * 84.16)+((1-(fB + fH)) * 28.05))

[0227] H [wt%] = 100 * (fH * 84.16) / ((fB * 56.11)+(fH * 84.16)+((1-(fB + fH)) * 28.05))

[0228] References:

[0229] Klimke, K., Parkinson, M., Piel, C., Kaminsky, W., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2006; 207:382.

[0230] Parkinson, M., Klimke, K., Spiess, H.W., Wilhelm, M., Macromol. Chem. Phys. 2007; 208:2128.

[0231] Pollard, M., Klimke, K., Graf, R., Spiess, H.W., Wilhelm, M., Sperber, O., Piel, C., Kaminsky, W., Macromolecules 2004; 37:813.

[0232] Filip, X., Tripon, C., Filip, C., J. Mag. Resn. 2005, 176, 239.

[0233] Griffin, J.M., Tripon, C., Samoson, A., Filip, C., and Brown, S.P., Mag. Res. in Chem. 2007 45, S1, S198.

[0234] Castignolles, P., Graf, R., Parkinson, M., Wilhelm, M., Gaborieau, M., Polymer 50(2009)2373

[0235] Busico, V., Cipullo, R., Prog. Polym. Sci. 26(2001)443.

[0236] Busico,V.,Cipullo,R.,Monaco,G.,Vacatello,M.,Segre,AL,Macromoleucles30(1997)6251.

[0237] Zhou,Z.,Kuemmerle,R.,Qiu,X.,Redwine,D.,Cong,R.,Taha,A.,Baugh,D.Winniford,B.,J.Mag.Reson.187(2007)225.

[0238] Busico,V.,Carbonniere,P.,Cipullo,R.,Pellecchia,R.,Severn,J.,Talarico,G.,Macromol.Rapid Commun.2007,28,1128.

[0239] Resconi,L.,Cavallo,L.,Fait,A.,Pimontesi,F.,Chem.Rev.2000,100,1253.

[0240] Dart Drop Intensity (DDI): Determination of impact resistance by free falling dart method

[0241] DDI was measured according to ISO 7765-1:1988 / Method A on films (non-oriented films and laminates) produced as shown below. This test method covers the determination of the energy that will cause film failure under specified conditions of impact with a dart falling freely from a specified height, which will cause 50% of the test specimens to fail (Step Method A). A uniform increment of the missile mass was used during the test, and after each specimen test, the missile weight was reduced or increased by a uniform increment depending on the observed result (failure or no failure) of the specimen.

[0242] Standard conditions:

[0243] Adjustment time: >96h at 50±2℃±10%rh

[0244] Test temperature: 23℃

[0245] Dart head material: phenolic resin

[0246] Dart diameter: 38mm

[0247] Drop height: 660mm

[0248] result:

[0249] Impact failure weight - 50% [g]

[0250] Tensile modulus

[0251] The tensile tests were carried out according to ISO 527-3, and in addition the modulus of elasticity (secant modulus between 0.05% and 0.25% elongation) was determined. Type 2 (parallel-sided specimens) specimens were used.

[0252] During the test, the specimen is extended along its long axis and the tensile properties are determined at a constant test speed (crosshead speed) until the specimen breaks. During this procedure, the load borne by the specimen and the elongation measured by the crosshead are measured.

[0253] Standard conditions:

[0254] Adjustment time: >96h at 50±2℃±10%rh

[0255] Test temperature: 23℃

[0256] Clamping distance: 100mm

[0257] Gauge length: 100mm

[0258] Secant modulus: 0.05%-0.25%

[0259] Test speed modulus: 1mm / min

[0260] Test speed: 200mm / min

[0261] Haze

[0262] Haze is measured according to ASTM D1003 test method (Method A - Hazemeter). This method covers the evaluation of specific light transmission and scattering properties of planar portions of materials, such as substantially transparent plastics.

[0263] The beam strikes the specimen and enters an integrating sphere. The interior of the sphere is uniformly coated with a matte white material to allow for diffusion. The detector in the sphere measures total transmittance, haze, and clarity (not part of ASTM D1003).

[0264] The incident light will be diffusely transmitted, changing the apparent quality of the product. This may be the result of scattering from the surface structure (roughness) or from within the particles, such as air inclusions, poorly dispersed pigments, dust inclusions or crystallization. As the roughness increases, the haze increases and the transmittance of the plastic decreases.

[0265] Standard conditions:

[0266] Adjustment time: >96h

[0267] Temperature: 23℃

[0268] Test Procedure: A-Haze Meter

[0269] Tear resistance (determined as Elmendorf tear (N) in machine direction (MD) and transverse direction (TD):

[0270] Tear resistance is measured according to ISO 6383-2 method. The force required to propagate a tear on a film sample is measured using a pendulum device and a constant radius specimen is used. The pendulum swings along an arc under the action of gravity, tearing the sample from the pre-cut slit. One side of the specimen is fixed by the pendulum and the other side is fixed by a fixed fixture.

[0271] The tear resistance is the force required to tear the sample. The relative tear resistance (N / mm) is then calculated by dividing the tear resistance by the thickness of the film.

[0272] Sealing start temperature (SIT); Sealing end temperature (SET), Sealing range

[0273] This method determines the sealing temperature range (sealing range) of polyethylene films, in particular blown films or cast films. The sealing temperature range is the temperature range over which the film can be sealed according to the conditions given below.

[0274] The lower limit (heat seal initiation temperature (SIT)) is the sealing temperature at which a seal strength of 5 N is achieved. The upper limit (seal end temperature (SET)) is achieved when the film sticks to the sealing device.

[0275] The measurements were performed according to a slightly modified ASTM F1921-12, where the test parameters sealing pressure, cooling time and test speed were modified. The force / temperature curve was continued until thermal failure of the film. The sealing range was determined on a 40 μm thick single-layer test blown film on a J&B Universal Sealer Model 4000, where the following additional parameters were used:

[0276] Adjustment time: >96h

[0277] Sample width: 25mm

[0278] Sealing pressure: 0.4N / mm 2 (PE)

[0279] Sealing time: 1 second

[0280] Delay time: 30 seconds

[0281] Sealing jaws size: 50x5 mm

[0282] Sealing jaws shape: flat

[0283] Sealing jaw coating: Niptef

[0284] Sealing temperature: ambient temperature -240℃

[0285] Sealing temperature interval: 5°C

[0286] Starting temperature: 50°C Clamp separation rate: 42 mm / s

[0287] Membrane sample preparation

[0288] Film samples were produced on a small-scale laboratory blown film line from COLLIN Lab&Pilot Solutions GmbH.

[0289] The line consisted of an extruder with a screw diameter of 25 mm and an aspect ratio of 30. The extruder temperature was set at 200 °C, the melt temperature was 202-204 °C and was recorded after 45 minutes of process stabilization. The extruder was followed by a blow molding head equipped with The die was annular and the die gap was 1.5 mm. The line was running at a constant output of 6.49 kg / h and a line speed of 7.4 m / min. The blow-up ratio (BUR) of the film bubble was 2.5:1, resulting in a lay-flat width of 196 mm. The film thickness produced was 40 μm.

[0290] The produced membranes were used for the following mechanical tests.

[0291] Example:

[0292] Catalyst Example: Catalyst Preparation of CAT1 for Examples IE1 and IE2 of the Present Invention and Comparative Example CE2:

[0293] SiO2 loading:

[0294] 10 kg of silica (PQ Corporation ES757, calcined at 600°C) was added from a feed bucket and inerted in the reactor until the O2 level reached less than 2 ppm.

[0295] Preparation of MAO / tol / MC:

[0296] At 25°C (oil circulation temperature) and 95rpm stirring, a 30wt% MAO toluene solution (14.1kg) was added from a balance to another reactor, followed by toluene (4.0kg). After adding toluene, the stirring speed was increased from 95rpm to>200rpm, with a stirring time of 30 minutes. Metallocene racemic-dimethylsilanediylbis{2-(5-(trimethylsilyl)furan-2-yl)-4,5-dimethylcyclopentadiene-1-yl}zirconium dichloride 477g was added from a metal cylinder, followed by 4kg toluene rinse (total toluene was 8.0kg). The reactor stirring speed was changed to 95rpm for MC feeding, returned to 200rpm and continued for 3h reaction time. After the reaction time, the MAO / tol / MC solution was transferred to a feed container.

[0297] Preparation of catalyst:

[0298] The reactor temperature was set to 10°C (oil circulation temperature) and stirring was adjusted to 40 rpm during the addition of MAO / tol / MC. MAO / tol / MC solution (22.2 kg) was added over 205 min, followed by a stirring time of 60 min (oil circulation temperature set to 25°C). After stirring, the "dry mix" was stabilized at 25°C (oil circulation temperature) for 12 h with a stirring speed of 0 rpm. The reactor was rotated 20° (back and forth) and stirred several times per hour at a speed of 5 rpm.

[0299] After stabilization, the catalyst was dried at 60°C (oil circulation temperature) for 2 h under a 2 kg / h nitrogen flow, followed by drying under vacuum for 13 h (same nitrogen flow rate, stirring at 5 rpm). The dried catalyst was sampled and the HC content was measured using a Sartorius moisture analyzer (model MA45) in a glove box using thermogravimetry. The target HC level was <2% (actual 1.3%).

[0300] Catalyst Example: Catalyst Preparation of CE1 (CAT2)

[0301] 130 g of the metallocene complex bis(1-methyl-3-n-butylcyclopentadienyl)zirconium dichloride (IV) (CAS no. 151840-68-5) and 9.67 kg of a 30% solution of commercially available methylaluminoxane (MAO) in toluene were combined and 3.18 kg of dried purified toluene were added. The complex solution thus obtained was added to 17 kg of a silica support Sylopol 55SJ (supplied by Grace) by very slow and uniform spraying over 2 hours. The temperature was kept below 30° C. After the complex was added at 30° C., the mixture was reacted for 3 hours.

[0302] polymerization:

[0303] The Borstar pilot plant had a three-reactor set-up (Loop 1 - Loop 2 - GPR1) and a prepolymerization loop reactor.

[0304] Table 1: Polymerization conditions of mMDPE-1, mMDPE-2, mMDPE-3 and mMDPE-4

[0305]

[0306]

[0307] The polymer was mixed with 0.027 wt% FX 5922 (BASF) and 0.24 wt% Irganox B 561 (BASF), compounded and extruded on a ZSK 57 twin-screw extruder, where the wt% is relative to the total weight of the composition (total of mMDPE powder + additives = 100%). The melt temperature was 224° C. and the production rate was 221 kg / h.

[0308] Table 2: Material properties of mMDPE-1, mMDPE-2, mMDPE-3 and mMDPE-4.

[0309] * Below detection limit

[0310] Single layer blown film

[0311] Table 3: Properties of blown films

[0312] IE1 IE2 CE1 CE2 TM / MD MPa 534 553 426 509 TM / TD MPa 644 679 478 596 DDI g 263 274 96 119 Relative tear resistance MD N / mm 23 17 14 27 Relative tear resistance TD N / mm 195 246 67 119 SIT 123 123 120 121 <![CDATA[TM(MD) * DDI / SIT]]> 1142 1232 341 501

[0313] As can be seen from the above table, the composition using the metallocene-catalyzed mMDPE according to the present invention has improved stiffness and impact resistance, and shows the best balance between stiffness, impact resistance and sealing. In addition, the mMDPE according to the present invention has improved relative tear resistance, especially relative tear resistance in the transverse direction.

Claims

1. A metallocene-catalyzed multimodal medium density polyethylene (mMDPE) consisting of (i) 40.0 to 60.0 wt% of a polyethylene component (A), based on the total weight of the mMDPE, and (ii) 40.0 to 60.0 wt% of a polyethylene component (B), based on the total weight of the mMDPE, wherein the polyethylene polymer component (A) has 950 to 980 kg / m 3 density within the range (ISO 1183), and MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 2.0 to 500.0 g / 10 min; The polyethylene component (B) has 900 to 925 kg / m 3 density within the range (ISO 1183), and MFR2 in the range of 0.0001 to 1.0 g / 10 min (190°C, 2.16 kg, ISO 1133); Among them, metallocene-catalyzed medium-density polyethylene (mMDPE) has 932 to 955 kg / m 3 Density in the range (ISO 1183), MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.01 to 1.0 g / 10 min, and MFR in the range of 25 to 100 21 (190℃, 21.6kg, ISO 1133) and MFR2 (190℃, 2.16kg, ISO 1133) Ratio MFR 21 / MFR2.

2. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to claim 1, wherein the metallocene-catalyzed mMDPE has 935 to 950 kg / m 3 , preferably 938 to 945 kg / m 3 Density within the range (ISO1183) and / or an MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 0.05 to 0.90 g / 10 min, preferably 0.10 to 0.80 g / 10 min, more preferably 0.20 to 0.70 g / 10 min, and / or MFR in the range of 8.0 to 50.0 g / 10 min, preferably in the range of 10.0 to 45.0 g / 10 min, more preferably in the range of 12.0 to 40.0 g / 10 min, most preferably in the range of 15.0 to 35.0 g / 10 min 21 (190°C, 21.6kg, ISO1133), and / or Flow rate ratio (FRR), MFR in the range of 35.0 to 80.0, preferably 45.0 to 70.0 21 / MFR2.

3. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to claim 1 or 2, wherein the metallocene-catalyzed mMDPE has A molecular weight distribution (MWD), Mw / Mn, in the range of 4.0 to 12.0, preferably 5.0 to 11.0, more preferably 6.0 to 10.0, and / or FRR / MWD ratio in the range of 5.0 to 12.0, preferably 6.0 to 11.0, more preferably 7.0 to 10.

0.

4. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 3, wherein the metallocene-catalyzed mMDPE further has one or more, or preferably all, of the following properties: The weight average molecular weight Mw is at least 100000 g / mol, preferably in the range of 102000 to 170000 g / mol, more preferably 105000 to 150000 g / mol, still more preferably 1070000 to 135000 g / mol, and / or The z-average molecular weight Mz is between 250,000 and 500,000 g / mol, preferably between 270,000 and 450,000 g / mol, More preferably in the range of 300000 to 400000 g / mol, and / or The Mz / Mw ratio is in the range of 2.0 to 4.0, preferably 2.2 to 3.5, more preferably 2.3 to 3.2, and / or The FRR / (Mz / Mw) ratio is in the range of 12.0 to 30.0, preferably 14.0 to 26.0, more preferably 15.0 to 24.

0.

5. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 4, wherein in the metallocene-catalyzed mMDPE, The polyethylene component (A) has a molecular weight of 955 to 975 kg / m 3 , preferably 960 to 972 kg / m 3, more preferably 962 to 970 kg / m 3 and a density in the range of 10 to 400 g / 10 min, preferably 50 to 300 g / 10 min, more preferably an MFR2 (190° C., 2.16 kg, ISO 1133), and The polyethylene component (B) has a molecular weight of 905 to 920 kg / m 3 , more preferably 908 to 918 kg / m 3 , Even more preferably 910 to 916 kg / m 3 The density is in the range of 0.0003 to 0.5 g / 10 min. More preferred is an MFR2 (190° C., 2.16 kg, ISO 1133) in the range of 0.0005 to 0.1 g / 10 min, even more preferred is an MFR2 in the range of 0.0008 to 0.01 g / 10 min.

6. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 5, wherein in the metallocene-catalyzed mMDPE, polyethylene components (A) and / or (B) may be homopolymers or ethylene copolymers, Preferably, both components are ethylene copolymers, or the polyethylene component (A) is a homopolymer and the polyethylene component (B) is a copolymer, or vice versa, the polyethylene component (A) is a copolymer and the polyethylene component (B) is a homopolymer, more preferably, the polyethylene component (A) is a homopolymer and the polyethylene component (B) is a copolymer, most preferably, the polyethylene component (A) is a polyethylene homopolymer and the polyethylene component (B) is an ethylene-1-hexene copolymer.

7. A metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 6, wherein in the metallocene-catalyzed mMDPE, the polyethylene component (B) consists of a single ethylene copolymer or a single ethylene homopolymer, more preferably consists of a single ethylene copolymer, and the polyethylene component (A) consists of a single ethylene homopolymer or copolymer, or the polyethylene component (A) can be an ethylene homopolymer or copolymer mixture, which comprises a first ethylene polymer part (A-1) and a second ethylene polymer part (A-2) (for example consisting thereof), wherein both parts are either homopolymers or copolymers.

8. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to claim 7, wherein the polyethylene component (A) is a polyethylene homopolymer mixture comprising, preferably consisting of, a first ethylene homopolymer fraction (A-1) and a second ethylene homopolymer fraction (A-2), wherein the ethylene polymer portion (A-1) has MFR2 (190°C, 2.16 kg, 2.16 wt %) in the range of 5.0 to 100.0 g / 10 min, preferably 10.0 to 80.0 g / 10 min, more preferably 15.0 to 70.0 g / 10 min, even more preferably 20.0 to 60.0 g / 10 min ISO 1133), and 945 to 970 kg / m 3 , more preferably 950 to 965 kg / m 3 , even more preferably 952 to 962 kg / m 3 density within the range; and The ethylene polymer portion (A-2) has an MFR2 (190°C, 2.16 kg, ISO 1133) in the range of 100.0 to 1500.0 g / 10 min, preferably 200.0 to 1200.0 g / 10 min, more preferably 250.0 to 1000.0 g / 10 min, most preferably 280.0 to 800.0 g / 10 min, and 960 to 980 kg / m 3 , more preferably 965 to 980 kg / m 3 , even more preferably 970 to 978 kg / m 3 Density within the range.

9. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to claim 7 or 8, wherein the first and second ethylene polymer parts (A-1 and A-2) of the polyethylene component (A) are present in a weight ratio of 4:1 to 1:4, such as 3:1 to 1:3, or 2:1 to 1:2, or 1:1, based on the total weight of the polyethylene component (A).

10. The metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims, wherein the mMDPE is produced in the presence of a metallocene complex of formula (I): Wherein each X is independently a halogen atom, C 1-6 -alkyl, C 1-6 - alkoxy, phenyl or benzyl; Each Het is independently a monocyclic heteroaromatic group containing at least one heteroatom selected from O or S; L is -R'2Si-, wherein each R' is independently a C substituted with an alkoxy group having 1 to 10 carbon atoms. 1-20 -Hydrocarbon or C 1-10 -alkyl; M is Ti, Zr or Hf; Each R1 is the same or different, is C1-6 -alkyl or C 1-6 - alkoxy; Each n is 1 to 2; Each R 2 Same or different, is C 1-6 -alkyl, C 1-6 -alkoxy or -Si(R)3 group; Each R is optionally replaced by 1 to 3 C 1-6 -alkyl substituted C 1-10 - alkyl or phenyl; and Each p is from 0 to 1.

11. A film comprising the metallocene-catalyzed multimodal medium density polyethylene (mMDPE) according to any one of the preceding claims 1 to 10.

12. The film according to claim 11, wherein the film has at least one or more or preferably all of the following properties a) to c): a) a dart drop impact strength (DDI) of at least 150 g to at most 500 g, preferably 200 g to at most 450 g, more preferably 250 g to at most 400 g, measured on a 40 μm single layer test blown film according to ISO 7765-1:1988, and / or b) Tensile modulus (measured according to ISO 527-3 on 40 μm single-layer test blown film) in the machine direction (MD) direction in the range of >450 MPa to 1000 MPa, preferably 520 MPa to 800 MPa and in the transverse direction (TD) in the range of 500 MPa to 1000 MPa, preferably 600 MPa to 800 MPa, and / or c) Relative Elmendorf tear resistance measured according to ISO 6383 / 2 on blown films with a film thickness of 40 μm c1) at least 10 N / mm to at most 50 N / mm, preferably 12 N / mm to at most 40 N / mm, more preferably 15 N / mm to at most 30 N / mm in the machine direction (MD), and c2) at least 120 N / mm to at most 400 N / mm, preferably 150 N / mm to at most 350 N / mm, more preferably 180 N / mm to at most 300 N / mm in transverse direction (TD).

13. The film of claim 11, wherein the film is characterized by d) according to formula (I): Improved relationship between mechanical properties determined on a 40 μm test blown film and sealing properties, wherein the tensile modulus in the longitudinal direction is measured at 23° C. on a 40 μm test blown film according to ISO 527-3, DDI is the dart impact strength measured on a 40 μm test blown film according to ISO 7765-1:1988. SIT is the seal initiation temperature measured on a 40 μm test blown film as described in the experimental section, Preferably, TM(MD) * DDI / SIT>800, more preferably>1000.

14. The membrane according to claim 13, wherein the membrane satisfies parameter d) and additionally at least parameter a) of claim 12, more preferably satisfies parameter d) and additionally parameters a) and b) of claim 12, even more preferably satisfies parameter d) and additionally parameters a), b) and c2) of claim 12.

15. Use of the film according to any of the preceding claims 11 to 14 in packaging applications or as a layer in a multilayer polyethylene-based blown film, preferably as a core layer in a multilayer polyethylene-based blown film.

Citation Information

Patent Citations

  • Apparatus and method for producing ethylene polymer

    EP0479186A2

  • High solids slurry polymerization

    EP0891990A2

  • Polymerisation reactor

    EP1310295A1

  • Process and apparatus for producing olefin polymers

    EP1415999A1

  • Process for producing polyethylene

    EP1591460A1